PEMANFAATAN ANGGREK SEBAGAI BAHAN OBAT TRADISIONAL PADA ETNIS BATAK SUMATERA UTARA - Silalahi, Marina; Nisyawati, Nisyawati (BERITA BIOLOGI, 2015)
Sumatra has rich diversity of orchids. The local communities in Sumatra have been used orchids as a ornamental plant, food, and medicine. Research on utilitation of orchids as medicinal plants by ethnic Batak of North Sumatra was conducted using ethnobotanical methods. The objectives of the research was to know species of orchids that were used as medicinal plants by Batak ethnic in North Sumatra. Respond-ents consisted of traditional medicine plants traders in the traditional markets and traditional healers. We found as many as seven species of 6 genera of orchids have been used as traditional medicine. Those orchids used as medicine for fever, aphrodisiac, maintain stamina, respira-tory disorders, and gastrointestinal disorders.